272 10-YEAR FOLLOW-UP OF A RANDOMISED CONTROLLED TRIAL COMPARING NEOADJUVANT CHEMORADIOTHERAPY PLUS SURGERY VERSUS SURGERY ALONE FOR OESOPHAGEAL CANCER (CROSS). (14th September 2020) - Eyck, B; Lanschot, J; Hulshof, M; Wilk, B; Shapiro, J; Hagen, P; Nieboer, D; Berge Henegouwen, M; Wijnhoven, B; Laarhoven, H; Nieuwenhuijzen, G; Hospers, G; et al.
Abstract: : Neoadjuvant chemoradiotherapy according to the Dutch randomised controlled ChemoRadiotherapy for Oesophageal cancer followed by Surgery Study (CROSS) has become standard of care for patients with cancer of the oesophagus or oesophagogastric junction. The aim of this study was to provide more insight into the ultra-long-term impact of CROSS neoadjuvant chemoradiotherapy on survival and disease recurrence for patients with oesophageal cancer. Methods: Patients with locally advanced resectable squamous cell carcinoma or adenocarcinoma of the oesophagus or oesophagogastric junction were randomised between neoadjuvant chemoradiotherapy (five weekly cycles of intravenous carboplatin [AUC 2 mg/mL per min] and intravenous paclitaxel [50 mg/m 2 of body-surface area]) with concurrent 41.4 Gy radiotherapy given in 23 fractions of 1.8 Gy, 5 days per week) plus surgery (nCRT arm) versus surgery alone (surgery arm). Primary endpoint was overall survival, defined from date of randomisation to date of all-cause death or to last day of follow-up. Secondary endpoints were cause-specific mortality and conditional survival. Analysis was by intention-to-treat. Results: From 2004 through 2008, 178 patients were randomized to the nCRT arm and 188 to the surgery arm. Median follow-up for surviving patients was 146.6 months (IQR 133.5–157.2). Ten-year overall survival was 38% in the nCRT arm and 25% in the surgery arm (HR 0.68 [95%CI 0.53–0.87]). For patients with squamous cell carcinoma ten-year overall survival was 46% in the nCRT arm compared to 23% in the surgery arm. For patients with adenocarcinoma ten-year overall survival was 36% in the nCRT arm and 26% in the surgery arm. In the nCRT arm, ten-year oesophageal cancer-specific mortality was 47%. Conclusion: Survival benefit of patients with locally advanced resectable squamous cell carcinoma or adenocarcinoma of the oesophagus or oesophagogastric junction receiving neoadjuvant chemoradiotherapy persists for at least 10 years compared to patients undergoing surgery alone.